2022
DOI: 10.1038/s41388-022-02432-5
|View full text |Cite
|
Sign up to set email alerts
|

Loss of FGFR4 promotes the malignant phenotype of PDAC

Abstract: Transcriptomic analyses of pancreatic ductal adenocarcinoma (PDAC) have identified two major epithelial subtypes with distinct biology and clinical behaviours. Here, we aimed to clarify the role of FGFR1 and FGFR4 in the definition of aggressive PDAC phenotypes. We found that the expression of FGFR4 is exclusively detected in epithelial cells, significantly elevated in the classical PDAC subtype, and associates with better outcomes. In highly aggressive basal-like/squamous PDAC, reduced FGFR4 expression aligns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Therefore, we decided to focus on SEMA3A and SEMA3C. In keeping with the correlative analyses, we identified higher SEMA3A expression in whole cell lysates from cells with prominent squamous features including expression of TP63/ΔNp63 (Colo357, L3.6pl, BxPC3) or CK5 (Hs766t, see D’Agosto et al [27]) ( Figure 1C ). SEMA3C showed a more promiscuous pattern of expression in human cell lines ( Figure S1C ).…”
Section: Resultssupporting
confidence: 55%
“…Therefore, we decided to focus on SEMA3A and SEMA3C. In keeping with the correlative analyses, we identified higher SEMA3A expression in whole cell lysates from cells with prominent squamous features including expression of TP63/ΔNp63 (Colo357, L3.6pl, BxPC3) or CK5 (Hs766t, see D’Agosto et al [27]) ( Figure 1C ). SEMA3C showed a more promiscuous pattern of expression in human cell lines ( Figure S1C ).…”
Section: Resultssupporting
confidence: 55%
“…The HNF1A gene encodes hepatocyte nuclear factor-1 alpha (HNF-1α), which is important in the pancreas and liver. It acts as a transcription factor to regulate insulin, controls genes that regulate cell growth and survival, and acts as a tumor suppressor [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that querying bulk transcriptional datasets from tissues with different neoplastic cell content is a viable strategy to localise the cellular compartment contributing to gene expression differences between molecular subtypes 74 . Using the same approach, we show that MAPK transcriptional signatures were particularly elevated in basal-like tumours from the TCGA cohort 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with previous observation from Miyabayashi and colleagues showing that RAS signalling hyperactivation is not fundamental for the definition of the basal-like/squamous subtype in the epithelial compartment 27 . We have previously shown that querying bulk transcriptional datasets from tissues with different neoplastic cell content is a viable strategy to localise the cellular compartment contributing to gene expression differences between molecular subtypes 74 . Using the same approach, we show that MAPK transcriptional signatures were particularly elevated in basal-like tumours from the TCGA cohort 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation